REPRESENTASI PEREMPUAN DALAM KOLOM HUMOR SI PALUI DI BANJARMASIN POST - Vidiadari, Irene Santika (Informasi, 2017)
The focus of this paper is the representation of women on Banjarmasin Post's humour column, "Si Palui," whose stories are either about daily lives or domestic issues. On the latter topic, the theme which regularly appears is marital problems such as poligamy, divorce, and sexuality. On this column, women characters are merely supporting casts and, hence, are subordinated. This research applies the critical language element of the micro level of Norman Fairclough's Critical Discourse Analysis in order to understand the representation issues through language: semantics, syntax, and lexycon. Th result shows that the representation of women on Si Palui is categorized into three: as widows, wives, and other kinds of women. The widows are illustrated as having plumpy body and always expecting to get married, though the representation emphasizes on the kind of flirtious widows adored by men. The wives are represented as the sexual objects of their husband. Meanwhile other kinds of women, such as mother-in-laws, are fussy, and single women are agressive. Abstrak Tulisan ini berfokus untuk melihat representasi perempuan dalam kolom humor berbahasa Banjar, Si Palui di Banjarmasin Post. Humor Si Palui menceritakan kejadian sehari-hari dan membahas persoalan rumah tangga. Pada cerita Palui yang bertema rumah tangga, beberapa tema yang sering hadir adalah poligami, perceraian, dan seksualitas suami istri. Pada kolom Si Palui, tokoh perempuan hadir sebagai figuran dan subordinat. Penelitian ini menggunakan elemen critical language dari level mikro pada analisis wacana Fariclough untuk membedah persoalan representasi melalui aspek bahasa: semantik, sintaksis dan leksikon. Hasil penelitian ini menunjukkan bahwa representasi perempuan dalam teks Si Palui terbagi menjadi tiga: sebagai janda, istri, dan status perempuan lain digambarkan berbeda-beda. Tokoh janda digambarkan sebagai tokoh yang berbadan montok, manja, dan ingin segera menikah. Tokoh janda yang mendapat penegasan dalam kolom Palui adalah janda kembang yang menjadi idola laki-laki. Tokoh istri digambarkan sebagai objek seksual suaminya. Perempuan lain, seperti mertua, digambarkan cerewet, dan perempuan lajang diceritakan agresif.